Radiation resistance of nano-crystalline iron: Coupling of the fundamental segregation process and the annihilation of interstitials and vacancies near the grain boundaries. (1st May 2016) - Li, Xiangyan; Liu, Wei; Xu, Yichun; Liu, C.S.; Pan, B.C.; Liang, Yunfeng; Fang, Q.F.; Chen, Jun-Ling; Luo, G.-N.; Lu, Guang-Hong; Wang, Zhiguang
Abstract: Finding novel nuclear materials with high radiation resistance is very important for the nuclear industry and requires the understanding of the self-healing of radiation damage in such novel materials as nano-crystalline iron. Combining molecular dynamics simulations, molecular statics calculations and the object kinetic Monte Carlo method, we found that the self-healing capability of nano-crystalline iron is closely related to the coupling of the individual fundamental segregation and annihilation processes of vacancies and interstitials near the grain boundary (GB). Statically, both near the GB and at the GB, a low-energy-barrier/barrier-free region forms around the interstitial which promotes the annihilation of vacancies. The annihilation process was found to always involve the collective motion of multiple atoms due to the recovery of the strained atoms around the interstitial. Dynamically, the annihilation involves two coupled processes. Before segregating into the GB, the interstitial annihilates lots of vacancies near the GB as it diffuses near the GB together with the low-barrier region. In addition, although the interstitial is tightly bound to the GB after segregation, it efficiently removes the vacancies near the GB while moving along the GB, with the low-barrier region extending into the neighborhood of the GB and even into the grain interior. These two mechanisms were found to work at low temperatures, even temperatures where the vacancy was immobile. This study revealed the interaction of the major radiation defects at different scales and thereby uncovered the origin of the high radiation resistance of nano-crystalline iron. Graphical abstract: